Performance of Globally Most Valued Brands – A Comparative Study of Service and Product Brands - Rentala, Satyanarayana (Journal of Contemporary Research in Management (JCRM), 2013)
Creating and maintaining brand identity is regarded as a formative brand building step with the benefits contributing to the creation of valuable brands. Consequently, research that provides brand identity management insights has the potential to be of considerable academic and managerial interest. This study analyses the performance of the service sector brands and compares the performance of global service sector brands with global product brands. The study presents an analysis of secondary data from the research undertaken by ‘Interbrand’ – one of the world’s largest branding consulting companies. This empirical study analyzes the performance of service and product brands of different industries during a twelve year period from 2001-2012 and highlights the differences between the performance of service brand and product brands. The study will attempt to bring out the growth/de-growth patterns of globally most valued brands belonging to various product categories. The findings of the study will highlight the marketing strategies of the globally most valuable service and product brands in comparison to their competitors. Key Words: Interbrand, Most Valued Brands, Product Brand and Service Brand